HPA axis genetic variation, cortisol and psychosis in major depression - Schatzberg, A F; Keller, J; Tennakoon, L; Lembke, A; Williams, G; Kraemer, F B; Sarginson, J E; Lazzeroni, L C; Murphy, G M (Molecular psychiatry, 2014)
Genetic variation underlying hypothalamic pituitary adrenal (HPA) axis overactivity in healthy controls (HCs) and patients with severe forms of major depression has not been well explored, but could explain risk for cortisol dysregulation. In total, 95 participants were studied: 40 patients with psychotic major depression (PMD); 26 patients with non-psychotic major depression (NPMD); and 29 HCs. Collection of genetic material was added one third of the way into a larger study on cortisol, cognition and psychosis in major depression. Subjects were assessed using the Brief Psychiatric Rating Scale, the Hamilton Depression Rating Scale and the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders. Blood was collected hourly for determination of cortisol from 1800 to 0900 h and for the assessment of alleles for six genes involved in HPA axis regulation. Two of the six genes contributed significantly to cortisol levels, psychosis measures or depression severity. After accounting for age, depression and psychosis, and medication status, only allelic variation for the glucocorticoid receptor (GR) gene accounted for a significant variance for mean cortisol levels from 1800 to 0100 h ( r 2 =0.288) and from 0100 to 0900 h ( r 2 =0.171). In addition, GR and corticotropin-releasing hormone receptor 1 (CRHR1) genotypes contributed significantly to psychosis measures and CRHR1 contributed significantly to depression severity rating.